Note : Lack of influence of adherent Lactobacillus isolates on the attachment of Escherichia coli to the intestinal epithelial cells of chicken in vitro - Jin, L.Z.; Ho, Y.W.; Abdullah, N.; Ali, M.A. (1998)
Two Lactobacillus isolates, Lact. acidophilus I 26 and Lact. fermentum I 25, were selected, based on their poor aggregation with Escherichia coli and strong ability to adhere to ileal epithelial cells (IEC), to study in vitro interactions with E. coli O1: K1, O2: K1 and O78: K80 in an IEC radioactive- assay under the conditions of exclusion (lactobacilli and IEC, followed by the addition of E. coli), competition (lactobacilli, IEC and E. coli together) and displacement (E. coli and IEC, followed by the addition of lactobacilli). The results indicated that Lact. acidophilus I 26 and Lact. fermentum I 25 could not significantly reduce the attachment of E. coli O1: K1, O2:K1 and O78:K80 to IEC under the three conditions tested in vitro, except that the attachment of E. coli O1:K1 was slightly reduced by Lact. fermentum I 25 in the test for competition.